The Manchester Procedure as a Uterine-Preserving Alternative for Uterine Prolapse Due to Cervical Elongation: A Short- and Mid-Term Clinical Analysis - Claudia Liger Guerra; Lorena Sabonet Morente; Juan Manuel Hidalgo Fernandez; Manuel Navarro Romero; Cristina Espada Gonzalez; Jesus S. Jimenez-Lopez (Medicina, 2025)
Background and Objectives: Pelvic organ prolapse (POP) is a prevalent condition that negatively impacts women’s quality of life. Uterine-preserving procedures are increasingly demanded by patients with uterine prolapse, particularly when associated with true cervical elongation. The Manchester procedure, historically used for uterine preservation, has regained interest due to its effectiveness and low morbidity. This study aims to evaluate the anatomical and functional outcomes of the Manchester procedure in women with uterine prolapse due to cervical elongation, assessing patient satisfaction and associated clinical factors. Materials and Methods: We conducted a retrospective, observational, single-center study at the Regional University Hospital of Málaga, Spain, including patients undergoing the Manchester procedure between January 2017 and December 2022. Inclusion criteria required a diagnosis of uterine prolapse due to clinically confirmed true cervical elongation. Surgical details, complications, and postoperative outcomes were recorded. Patient satisfaction was assessed using a Likert scale during follow-up visits. Results: A total of 38 patients were included, with a mean age of 48.7 years. All presented with symptomatic uterine prolapse and elongated cervix (>5 cm). The anatomical success rate was 97%, with only one case of symptomatic recurrence. The most common early postoperative complication was urinary tract infection (10.5%). The average follow-up duration was 18.6 months. A high level of satisfaction was recorded: 94.8% of patients were either “very satisfied” (73.7%) or “satisfied” (21.1%), and only 5.3% reported dissatisfaction. Multicompartmental repair (anterior and/or posterior colporrhaphy) improved satisfaction outcomes. Conclusions: The Manchester procedure is a safe, effective uterine-sparing surgical option for patients with cervical elongation-related uterine prolapse. It demonstrates a high anatomical success rate and low morbidity, with excellent patient satisfaction. Comprehensive preoperative assessment and addressing modifiable risk factors such as obesity and smoking are key to optimizing results. Further prospective studies are needed to assess long-term durability and quality-of-life outcomes.